Small molecule-induced cellular conversion. (22nd August 2017) - De, Debojyoti; Halder, Debasish; Shin, Injae; Kim, Kyeong Kyu
Abstract : This review highlights recent advances made using small molecules that promote changes in the fate of cells. Abstract : Over the last decade, the development of methods to promote conversion of one type of cell to a specific type of another cell (or change of cell fate) has received great attention in basic biological research and therapeutic applications. A precise, reproducible and safe protocol for inducing this change is a prerequisite for cellular conversion. Although genetic manipulation, which relies on the introduction of specific genes into cells, is a promising approach, the results of initial investigations have highlighted serious safety concerns associated with forced ectopic gene expression with unpredictable side effects. Alternatively, a chemical approach that relies on the use of small molecules to modulate the cell fate has great potential in terms of precise control and clinical safety. In addition, the ease of application, reproducibility and scalability are features that make a small molecule-based approach an extraordinary resource for this purpose. In this review we summarize methods which have been devised to identify small molecules that induce cellular conversion and highlight recent advances made using small molecule modulators to induce changes in the fate of cells.